N-(2-ferrocene-ethyl)maleimide: a new electroactive sulphydryl-specific reagent for cysteine-containing peptides and proteins. - Di Gleria, K; Hill, H; Wong, L (1996)
We report the synthesis and application of a specific electroactive label, N-(2-ferrocene-ethyl)maleimide, which provides new redox properties to organic compounds and proteins possessing sulphydryl groups. Its reaction conditions with the cysteine-containing peptide, glutathione, and a terminal monooxygenase enzyme, cytochrome P450cam are presented. The labelled peptide and enzyme acquired reversible electrochemical properties due to the attached ferrocene moiety.